Synthesis and Characterization of Some Homonuclear Bimetallic Complexes with Macrocyclic Ligands: A Photoelectron Spectroscopic Study - Kumar, Abhishek; Malviya, Shishir; Kushwaha, Rajesh Kumar; Srivastava, Shekhar (Asian Journal of Chemistry, 2017)
We have synthesized bimetallic macrocyclic complexes through chemical condensation method by using pyridine-2,6-dicarboxaldehyde with 1,2-bis(2-aminoethoxy) ethane where L is the macrocyclic ligand. The synthesized complexes were characterized by elemental analysis, IR, XPS data, NMR and UV-visible spectroscopy.